FEATURES OF USING INDIVIDUALIZED STANDARD VALUES FOR THE INCISORS’ POSITIONS ACCORDING TO С. STEINER IN UKRAINIAN YOUNG MEN AND GIRLS - Dmitriev, М.О.; Trofimenko, Yu.Yu.; Cherkasova, O.V.; Kernychnyi, V.V.; Gunas, I.V. (World of Medicine and Biology, 2020)
The purpose of the study is to investigate the correctness of the use of the recommended indexes of the position of the central incisors according to the data obtained by S. Stainer for Ukrainian young men and women with orthognathic bite. Cephalometric analysis was performed using OnyxCeph 3D pro, statistical analysis, construction of polynomial and regression models was performed in MS Excell and "Statistica 6.0". Analysis of the distribution of angular and linear indices of the position of the central incisors in Ukrainian young men and women revealed significant variability with respect to the ANB angle. Therefore, to perform more accurate diagnosis and treatment planning for individual human characteristics for Ukrainian young men and women in the diagnostic cephalometric method S. Stainer it is recommended to use the developed prognostic models for determining the linear and angular indicators of the position of the central incisors of the upper and lower jaw.
Keywords: central incisors; С. Stainer cephalometric analysis; Ukrainian young men and girls